Pigment epithelial-derived factor gene loaded novel COOH-PEG-PLGA-COOH nanoparticles promoted tumor suppression by systemic administration - Yu T (Dove Medical Press, 2016)
Ting Yu,1,* Bei Xu,1,* Lili He,2 Shan Xia,3 Yan Chen,1 Jun Zeng,1 Yongmei Liu,1 Shuangzhi Li,1 Xiaoyue Tan,4 Ke Ren,1 Shaohua Yao,1 Xiangrong Song1 1State Key Laboratory of Biotherapy and Cancer Center, West China Hospital, Sichuan University, and Collaborative Innovation Center for Biotherapy, 2College of Chemistry and Environment Protection Engineering, Southwest University for Nationalities, 3Central Laboratory, Science Education Department, Chengdu Normal University, Chengdu, Sichuan, 4Department of Pathology/Collaborative Innovation Center of Biotherapy, Medical School of Nankai University, Tianjin, People’s Republic of China *These authors contributed equally to this work Abstract: Anti-angiogenesis has been proposed as an effective therapeutic strategy for cancer treatment. Pigment epithelium-derived factor (PEDF) is one of the most powerful endogenous anti-angiogenic reagents discovered to date and PEDF gene therapy has been recognized as a promising treatment option for various tumors. There is an urgent need to develop a safe and valid vector for its systemic delivery. Herein, a novel gene delivery system based on the newly synthesized copolymer COOH-PEG-PLGA-COOH (CPPC) was developed in this study, which was probably capable of overcoming the disadvantages of viral vectors and cationic lipids/polymers-based nonviral carriers. PEDF gene loaded CPPC nanoparticles (D-NPs) were fabricated by a modified double-emulsion water-in-oil-in-water (W/O/W) solvent evaporation method. D-NPs with uniform spherical shape had relatively high drug loading (~1.6%), probably because the introduced carboxyl group in poly (D,L-lactide-co-glycolide) terminal enhanced the interaction of copolymer with the PEDF gene complexes. An excellent in vitro antitumor effect was found in both C26 and A549 cells treated by D-NPs, in which PEDF levels were dramatically elevated due to the successful transfection of PEDF gene. D-NPs also showed a strong inhibitory effect on proliferation of human umbilical vein endothelial cells in vitro and inhibited the tumor-induced angiogenesis in vivo by an alginate-encapsulated tumor cell assay. Further in vivo antitumor investigation, carried out in a C26 subcutaneous tumor model by intravenous injection, demonstrated that D-NPs could achieve a significant antitumor activity with sharply reduced microvessel density and significantly promoted tumor cell apoptosis. Additionally, the in vitro hemolysis analysis and in vivo serological and biochemical analysis revealed that D-NPs had no obvious toxicity. All the data indicated that the novel CPPC nanoparticles were ideal vectors for the systemic delivery of PEDF gene and might be widely used as systemic gene vectors. Keywords: pigment epithelium-derived factor gene, nanoparticles based on PLGA derivative, gene delivery, systemic delivery, tumor